Human schistosomiasis in the post mass drug administration era. Issue 2 (February 2017) - Mutapi, Francisca; Maizels, Rick; Fenwick, Alan; Woolhouse, Mark
Summary: Profound changes are occurring in the epidemiology of schistosomiasis, a neglected tropical disease caused by a chronic infection with parasitic helminths of the genus Schistosoma . Schistosomiasis currently affects 240 million people worldwide, mostly in sub-Saharan Africa. The advent and proliferation of mass drug administration (MDA) programmes using the drug praziquantel is resulting in substantial increases in the number of people, mainly children aged 6–14 years, being effectively treated, approaching the point where most people in endemic areas will receive one or more treatments during their lifetimes. Praziquantel treatment not only cures infection but also frees the host from the powerful immunomodulatory action of the parasites. The treatment simultaneously enhances exposure to key parasite antigens, accelerating the development of protective acquired immunity, which would take many years to develop naturally. At a population level, these changes constitute a substantial alteration to schistosome ecology in that the parasites are more likely to be exposed not only to praziquantel directly but also to hosts with altered immune phenotypes. Here, we consider the consequences of this for schistosome biology, immunoepidemiology, and public health. We anticipate that there could be substantial effects on chronic pathology, natural immunity, vaccine development strategies, immune disorders, and drug efficacy. This makes for a complex picture that will only become apparent over decades. We recommend careful monitoring and assessment to accompany the roll-out of MDA programmes to ensure that the considerable health benefits to populations are achieved and sustained.